Competency Analysis and Its Relevance to the Career Success of Sharia Accounting Graduates in The Digital Era - Nur Indah Aulia; Dewi Febriani (Muhasabatuna : Jurnal Akuntansi Syariah, 2025)
This study examines the effect of graduate competencies on career success in the digital era and assesses the relevance of the Sharia Accounting curriculum to graduates’ career outcomes. A quantitative approach was employed using purposive sampling, with data collected through questionnaires administered to Sharia Accounting graduates of IAI Tazkia (cohorts 14–18). The data were analyzed using descriptive statistics and Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that graduate competencies have a significant positive effect on career success in the digital era, while curriculum relevance does not exhibit a direct effect. This study recommends continuous curriculum enhancement to align with industry dynamics and labor market needs. The study is limited by its single-institution sample, which may restrict the generalizability of the findings.